2015
DOI: 10.1088/0004-637x/799/2/172
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Kinematics and Structural Properties of Virgo Cluster Dwarf Early-Type Galaxies From the Smakced Project. Iii. Angular Momentum and Constraints on Formation Scenarios

Abstract: We analyze the stellar kinematics of 39 dwarf early-type galaxies (dEs) in the Virgo cluster. Based on the specific stellar angular momentum λ Re and the ellipticity, we find 11 slow rotators and 28 fast rotators. The fast rotators in the outer parts of the Virgo cluster rotate significantly faster than fast rotators in the inner parts of the cluster. Moreover, 10 out of the 11 slow rotators are located in the inner 3 • (D < 1 Mpc) of the cluster. The fast rotators contain subtle disky structures that are visi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 85 publications
13
59
1
1
Order By: Relevance
“…The x-shapes found for VCC1261, VCC1528, and VCC1545 in the g-band residual images are typical of disky and boxy isophotes (see Figure 10). These three dEs are slow rotators based on the stellar rotation speed estimate by Toloba et al (2014aToloba et al ( , 2015. See Table 1 for a summary of the main properties of these dEs.…”
Section: Analysis Of Globular Cluster Systems From the Literaturementioning
confidence: 98%
See 3 more Smart Citations
“…The x-shapes found for VCC1261, VCC1528, and VCC1545 in the g-band residual images are typical of disky and boxy isophotes (see Figure 10). These three dEs are slow rotators based on the stellar rotation speed estimate by Toloba et al (2014aToloba et al ( , 2015. See Table 1 for a summary of the main properties of these dEs.…”
Section: Analysis Of Globular Cluster Systems From the Literaturementioning
confidence: 98%
“…The stellar kinematics are available for VCC1545 and VCC1861. While VCC1545 rotates at a speed of ∼25km s −1 (Chilingarian 2009), VCC1861 is not rotating (its stellar rotation is 5.3 ± 2.5 km s −1 ; Toloba et al 2011Toloba et al , 2014aToloba et al , 2015. See Table 1 for a summary of the main properties of these dEs.…”
Section: Globular Cluster Systems Of Vcc1539 Vcc1545 and Vcc1861mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this can only be applied to relatively bright objects (m < 24 r mag arcsec −2 ), which limits the study of the internal properties of spatially resolved galaxies to nearby objects. Some examples of integrated light spectroscopic studies of spatially resolved dwarf galaxies are reported in Geha et al (2002Geha et al ( , 2003, de Rijcke et al (2005), Koleva et al (2009), Toloba et al (2009Toloba et al ( , 2011Toloba et al ( , 2014aToloba et al ( , 2014bToloba et al ( , 2015, and Ryś et al (2013). Here we describe a new spectroscopic technique that allows for kinematic and metallicity studies of faint satellites and streams beyond the Local Group and up to a distance of ∼4 Mpc.…”
Section: Introductionmentioning
confidence: 99%